2020
DOI: 10.21608/ejchem.2020.43675.2881
|View full text |Cite
|
Sign up to set email alerts
|

Sources of Salinity and Suitability for Irrigation and Drinking Use of the Groundwater of Northwest of ElMinia, Upper Egypt.

Abstract: The present work is devoted to determine sources of groundwater salinity and suitability of its use for irrigation and drinking in northwest ElMinia, Upper Egypt. This information is important for sustainable and reliable development of the groundwater resources. A hydrochemical study using results of major ions and trace elements analysis of 43 groundwater samples collected from the study area have been conducted in this work. The TDS and major ionic concentrations vary in considerably wide ranges, these incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
0
1
0
Order By: Relevance
“…The sodium adsorption ratio of groundwater in this study was almost less than 10 and fell under the category of S1 indicating low alkali hazards according to [79]. Additionally, Sallam et al [84] concluded that the same study area is in a low SAR hazard category.…”
Section: Sodium Adsorption Ratio (Sar)mentioning
confidence: 44%
“…The sodium adsorption ratio of groundwater in this study was almost less than 10 and fell under the category of S1 indicating low alkali hazards according to [79]. Additionally, Sallam et al [84] concluded that the same study area is in a low SAR hazard category.…”
Section: Sodium Adsorption Ratio (Sar)mentioning
confidence: 44%
“…The present abstraction from the Moghra aquifer system is about 1 billion cubic meters annually, ranging from 2000 to 15,000 ppm, especially after starting new reclamation project in 2022. The fissured limestone aquifer covers about 53% of Egypt's surface area, with a poor potentiality, and there is pumping at present from this aquifer due to low yield with salinity ranging from 2100 to 16,000 ppm [21]. The groundwater salinity classification is shown in Figure 8.…”
Section: Site Selection Criteria Using Gismentioning
confidence: 99%